Integrating Rice Crop Manager with ICT based tool for scaling out climate-smart agriculture interventions - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
During 2019, the rice crop manager tool was integrated into the web portal of common service centers. District managers of all the districts of Odisha were trained in a training of trainers mode, who in turn, trained the village level entrepreneurs to generate recommendations using the rice crop manager tool.